An investigation into the knowledge, perceptions and role of personal protective technologies in Zika prevention in Colombia (2020)
Although mosquito personal protective technologies (PPT), such as topical DEET or permethrin impregnated clothing, show high efficacy in laboratory studies, they frequently achieve poor population uptake. This is likely due to numerous factors, including high costs, dislike of the feel or smell of the product, and safety fears over the repellent chemicals. The targeted use of PPT to those at elevated risk of severe disease, such as pregnant women in Zika endemic regions, may help mitigate adverse outcomes from Zika virus infection. To explore ways of increasing the appeal of PPT, a focus group study was performed with pregnant women and women of reproductive age in two cities in Colombia. Although almost all participants had heard of Zika, not all pregnant women were aware of the potential for Zika-related birth defects. PPT products were generally viewed as effective, although many expressed fears that repeated exposure to chemicals may affect fetal development. There was limited trust over repellent-manufacturer claims of safety, and women from low socioeconomic groups believed PPT products to be unaffordable. Participants identified health centers as trusted sources of bite-prevention education, suggesting health workers should emphasize safety and efficacy of approved repellents.